Penyuluhan Kesehatan tentang Pencegahan dan Penanganan Anemia pada Siswi di MTS Al-Munawwar - Aditya Nur Wahyuni; Ade Koswara; Alda Nurani Asmara; Alfi Fadilah; Andini Zharfa Asmarani; Desry Desry; Dina Mega Tresna Irawan Pamungkas (Yayasan Inspirasi El Burhani, 2023)
Introduction: Anemia is a condition where there is a lack of hemoglobin which functions as a means of transporting oxygen throughout the body and can cause problems for the growth and development of adolescents. One of the efforts that can be made to prevent and treat anemia in young women is by conducting health education. Objective: The purpose of this community service is to educate in prevention of anemia in female students at MTs Al-Munnawar, Gegempalan Village, Cikoneng District. Method: This activity was carried out using the health education method to MTs students as many as 31 people who were used as participants. The material presented was regarding the prevention and treatment of anemia, as well as the extension workers also collaborating with public health center in checking hemoglobin. Media counseling using prower point which is used as material for presentation of the material. After the delivery of the material, the participants were evaluated by opening a question and answer session. Results: Based on the results of measuring hemoglobin levels, 22 participants experienced anemia and were less active in carrying out activities. After the presentation of the material, the respondents were able to answer questions about the material. Conclusion: Health education about the prevention and treatment of anemia in students has proven to be useful in increasing the knowledge and attitudes of adolescents in preventing anemia.